Analysis of primary and secondary lateral suspension system of railway vehicle / Mohd Hanif Harun … [et al.] - Harun, Mohd Hanif (Faculty of Mechanical Engineering (FKM) and UiTM Press, 2014)
The aim of this paper is to study the effect of primary and secondary suspensions of a railway vehicle on stability and passenger ride comfort. The possible improvement of conventional suspension without using a controllable suspension system is investigated. A linear 17 degree-of-freedom (DOF) railway vehicle model is used to study the vibration response of the railway vehicle body. The equations of motion that represent the dynamics of the railway vehicle were derived based on Newton laws to describe the lateral, yaw and roll motions of the vehicle body, bogies and also wheel-sets. The spring stiffnesses and damping coefficients of the primary and secondary suspensions were varied incrementally in order to observe the response of the railway vehicle body. The vehicle model was simulated with lateral sinusoidal track disturbance using Matlab-SIMULINK software. The simulation results showed that the railway vehicle stability is significantly affected by the values of primary suspension.